Insights Into Genetic and Molecular Elements for Transgenic Crop Development - Basso, Marcos Fernando; Arraes, Fabrício Barbosa Monteiro; Grossi-de-Sa, Maíra; Moreira, Valdeir Junio Vaz; Alves-Ferreira, Marcio; Grossi-de-Sa, Maria Fatima (Frontiers in Plant Science, 2020)
Climate change and the exploration of new areas of cultivation have impacted the yields of several economically important crops worldwide. Both traditional plant breeding based on planned crosses between parents with specific traits and genetic engineering to develop new biotechnological tools (NBTs) have allowed the development of elite cultivars with new features of agronomic interest. The use of these NBTs to search for agricultural solutions has gained prominence in recent years due to their rapid generation of elite cultivars that meet the needs of crop producers. The efficiency of these NBTs is closely related to the optimization or best use of their elements. Currently, several genetic engineering elements are used in synthetic biotechnology to successfully improve desirable traits or remove undesirable traits in crops. However, the features, drawbacks, and advantages of each of these are still not well understood and have not been fully exploited. Here, we provide a brief overview of the plant genetic engineering platforms used for proofs of concept and improvement of agronomic traits, review the major synthetic biotechnology elements and processes, and finally, present the major NBTs used to improve agronomic traits in socioeconomically important crops.